Enzymatic transesterification of coconut oil by using immobilized lipase on biochar: An experimental and molecular docking study. (14th August 2020) - Almeida, Lays C.; Barbosa, Milson S.; de Jesus, Felipe A.; Santos, Roberta M.; Fricks, Alini T.; Freitas, Lisiane S.; Pereira, Matheus M.; Lima, Álvaro S.; Soares, Cleide M. F.
Abstract: Guava seed biochar appears as a new alternative of the effective support to the immobilization of Burkholderia cepacia lipase (BCL) by physical adsorption. The objective of this work was to evaluate the potential of this immobilized biocatalyst in the transesterification reaction of crude coconut oil and ethanol and to understand the mechanism of the reaction through the study of molecular docking. The best loading of BCL was determined to be 0.15 genzyme /gsupport having a hydrolytic activity of 260 U/g and 54% immobilization yield. The products of transesterification reaction produced a maximum yield at 40 °C under different reaction conditions. The monoacylglycerols (MAGs) conversion of 59% was using substrate molar ratio oil:ethanol of 1:7 with the reaction time of 24 H. In addition, the highest ethyl esters yield (48%) had the molar ratio of 1:7 with the reaction time of 96 H and maximum conversion of diacylglycerols (DAGs) was 30% with the molar ratio of 1:6 with the reaction time of 24 H. Molecular Docking was applied to clarify the mechanisms of transesterification reaction at the molecular level. MAGs and DAGs are compounds with excellent emulsifying properties used in industrial production of several bioproducts such as cosmetic, pharmaceuticals, foods, and lubricants. Abstract : The potential of Burkholderia cepacia lipase immobilized on guava seed biochar by physical adsorption was evaluated in transesterification reaction of crude coconut oil and ethanol. In addition, molecular docking was carried out to understand the reaction mechanism.